Influence of instructor‐to‐student ratio for teaching suturing skills with models. Issue 3 (12th February 2021) - Hunt, Julie A.; Anderson, Stacy L.; Spangler, Dawn; Gilley, Robert
Abstract: Objective: To evaluate the influence of instructor to student ratio on the effectiveness and efficiency of teaching suturing skills to veterinary students. Study design: Prospective randomized study. Sample population: Second‐year veterinary students (N = 121). Methods: Students were randomly divided into three groups to participate in four 2‐hour skills laboratory sessions in which suturing of the subcutaneous tissue was taught by using a simple continuous pattern, suturing of the skin was taught by using continuous patterns, suturing of the skin was taught by using interrupted patterns, and suturing of hollow organs was taught by using inverting patterns. For each laboratory, the groups were taught by using instructor‐to‐student ratios of 1:6, 1:8, and 1:10 on a rotating basis. Students were surveyed at the end of each laboratory, and underwent individual performance assessments at the end of each laboratory session and again at the end of the semester in an objective structured clinical examination (OSCE). Results: For each of the four in‐laboratory assessments and the OSCE, no difference in performance was detected between groups. When they were surveyed, students in all groups reported that there was an adequate number of instructors in the laboratory and that they received help in a timely fashion when help was requested (median for all groups = agree). Conclusion: For students with prior surgical skills education and with the use of prelaboratory instructional videos, teaching at the 1:10 instructor‐to‐student ratio was efficient and effective. Clinical significance: Good educational outcomes may be reached with a 1:10 instructor‐to‐student ratio or, potentially, fewer instructors, depending on the educational aids present in the laboratory and students' prior level of experience.